2004
DOI: 10.1007/s00430-004-0230-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Epstein-Barr virus DNA from peripheral blood mononuclear cells in adult patients with systemic lupus erythematosus in Taiwan

Abstract: Epstein-Barr virus (EBV) has been found by many serology studies to be associated with systemic lupus erythematosus (SLE). However, the results of DNA studies have been conflicting. Therefore, instead of antibody to EBV, we studied the association between EBV DNA and SLE. In this case-control study in Taiwan, we enrolled 87 SLE patients and 174 age- and sex-matched controls. Peripheral blood mononuclear cells of SLE patients and matched controls were tested for EBV DNA by polymerase chain reaction (PCR) and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 21 publications
2
42
0
1
Order By: Relevance
“…Number of studies showed that SLE patients had higher anti-EBV response and EBV DNA burden [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Number of studies showed that SLE patients had higher anti-EBV response and EBV DNA burden [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased viral load in blood and saliva are frequent (Moon et al, 2004;Strauch et al, 1974). These data are further backed by DNA analysis in SLE patients (Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…LMP2A AID mice produced autoantibodies against dsDNA and cardiolipin and had detectable immune complex deposition in the kidney; LMP2A CD19 mice also produced anti-cardiolipin antibodies. EBV titers correlate with systemic lupus erythematosus disease activity in some patients (32)(33)(34)(35)(36). Both LMP2A CD19 and LMP2A AID mice exhibited hyperimmunoglobulinemia (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that impaired affinity maturation in GCs may lead to autoantibody production (31). EBV titers have been reported to correlate with disease activity in patients with systemic lupus erythematosus (32)(33)(34)(35)(36), suggesting a possible involvement of EBV infection in autoantibody production. Indeed, we detected anti-dsDNA antibodies only in sera of LMP2A AID mice (Fig.…”
Section: Lmp2a Expression In Gc B Cells Leads To Autoantibody Productionmentioning
confidence: 99%